The effect of irrigation service delivery and training in agronomy on crop choice in Tajikistan - Buisson, Marie-Charlotte; Balasubramanya, Soumya (Elsevier, 2019)
The aim of this paper is to analyze the effect of irrigation delivery services and agricultural extension services on crop choice in southern Tajikistan. This analysis is motivated by the government’s recent efforts to address the country’s severe malnutrition problem by supporting changes in irrigation service delivery and agronomy to increase diversity in agricultural production and consumption, in an environment where the cultivation of cotton had, until recently, been mandatory. Water management in Tajikistan has largely been transferred to the community through the creation of water users’ associations (WUAs), which were established between 2011 and 2013. While all WUAs received training to improve irrigation delivery services, some also received training in cultivating alternative crops and improving cultivation practices through agricultural extension services. Through specific empirical analysis conducted on a primary panel dataset of 1855 farms in southern Tajikistan, we identify the extent to which improvements in irrigation services, and agronomy training through extension services affect decisions pertaining to cultivated areas of cotton and wheat (the traditional crops) and the cultivated area and number of (newer) high-value crops. We also examine the effect of water delivery and agricultural extension services on crop diversity and cropping intensity (how often land is used in a calendar year). We find that improvements in irrigation delivery services affect cultivated areas of cotton and wheat. Cultivation of high value crops is significantly influenced by agricultural extension services. While cropping intensity depends on water delivery services, crop diversity depends on extension services. From a policy perspective, these results highlight the importance of agricultural programs for stimulating agricultural value added in landscapes historically characterized by limited crop choice and a collapse of the agricultural sector.